NUMERICAL SIMULATION OF COHESIVE SEDIMENT TRANSPORT IN JAKARTA BAY - I.M. Radjawane; F Riandini (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2009)
The 3D-numerical model has been applied to simulate the current circulation and cohesive sediment transport in the Jakarta Bay, Indonesia. Sediment load comes from 3 river mouths i.e. Angke River, Karang River, and Ancol River. The model was simulated to analyze the effect of tidal current and river discharge. A constant westerly and easterly wind was used as input of the model to see the influence of monsoonal season. The numerical result showed that the tidal current flows from east to western part of the bay during ebb tide and vice versa during flood tide. The surface current circulation was dominantlyinfluenced by the tidal current comparated with the wind and river discharge effects. Hight turbidity level was found near the river mounths with the range of 50 to 100 mg per l. This high in the offshore area of the bay the sediment concentration decreases up to 10 mg per l. The movement of sediments followed the current circulations. During the flood tide, the sediment concentratation from the mounth of Angke River moved to the western part of the bay. Model simulated for increasing the river discharge into two times showed that the sediment distributed to the offshore direction two time longer compare with the normal debit. The transport of sediment from the Angke and Karang Rivers to the offshore area reached up to 6 km, while it just reached plus minus 2,5 km from the Ancol River. Keyword: Numerical model, Cohesive sediment, Effect of tidal current and river discharge.